VD_FINDINFO Jug / 2013 / 322 vom 6. September 2013 - VD Tribunal cantonal (2013)
PRESCRIPTION, CONTRAT D'ENTREPRISE, DOMMAGE CONSÉCUTIF AU DÉFAUT, DÉFAUT DE LA CHOSE, ACTION EN DOMMAGES-INTÉRÊTSEN GÉNÉRAL | 363 CO, 371 al. 1 CO, 371 al. 2 CO, 41 CO, 243 CPC